Pengembangan E-LKPD Terintegrasi Data BMKG dalam Pembelajaran Termodinamika - Yasrifa Fitri Aufia; Hawinda Restu Putri; Nurma Mahendra Sani; Bella Yunisah Putri; Widayani; Triyanta (Postgraduate, University of Mataram, 2025)
This study aimed to develop an electronic student worksheet (E-LKPD) integrates real data from the Meteorology, Climatology, and Geophysics Agency (BMKG) for thermodynamics learning. The research employed the 4D development model (define, design, develop, and disseminate). At the define stage, the need for contextual learning media was identified, highlighting the importance of linking physics concepts with authentic climate data. The E-LKPD was designed with interactive and digital features to enhance student engagement. Validation by experts and teachers confirmed its validity and practicality. A classroom trial involving 35 students showed positive responses, improved conceptual understanding, and increased motivation. Observations further revealed that the integration of real climate data made physics learning more meaningful and engaging. In conclusion, the BMKG-based E-LKPD is a valid, practical, and effective learning resource that supports both conceptual mastery and student enthusiasm. Future research is recommended to examine its wider application in diverse classroom settings.